2015
DOI: 10.1007/s10840-015-0092-3
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Achieve Mapping Catheter in cryoablation for atrial fibrillation: a prospective randomized trial

Abstract: The use of the Achieve Mapping Catheter can reduce procedure and fluoroscopic durations compared with Lasso catheters in cryoablation for PAF after operators gained sufficient experience. The type of mapping catheter used does not affect procedure efficiency and safety by models of cryoballoon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…The mechanisms of recurrence and knowledge of site-specific pulmonary venous breakthrough may help modify the index procedure to be more robust. In addition, the utility of the Achieve™ (Medtronic, Inc., Minneapolis, MN) has been found to be effective at aiding in acute procedural success [13] and comparable to Lasso catheters [14], but has not been compared with ultrasound-guided roving map catheter technique allowing for direct visualization in real time. Given the lack of rigorous evaluation, the purpose of the study was to evaluate the mechanisms of recurrent atrial fibrillation (AF) after use of the Arctic Front Ablation system.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanisms of recurrence and knowledge of site-specific pulmonary venous breakthrough may help modify the index procedure to be more robust. In addition, the utility of the Achieve™ (Medtronic, Inc., Minneapolis, MN) has been found to be effective at aiding in acute procedural success [13] and comparable to Lasso catheters [14], but has not been compared with ultrasound-guided roving map catheter technique allowing for direct visualization in real time. Given the lack of rigorous evaluation, the purpose of the study was to evaluate the mechanisms of recurrent atrial fibrillation (AF) after use of the Arctic Front Ablation system.…”
Section: Introductionmentioning
confidence: 99%
“…In a very early stage cryoballoon ablation of AF was considered a sort of “anatomical procedure”, without the possibility to measure electrophysiological signals during cryoenergy delivery. A significant technical improvement of the cryoballoon technique was the possibility to associate to the single shot balloon ablation technology, the possibility to record electrophysiological signals obtained by means of the ACHIEVE mapping catheter [ [15] , [16] , [17] ]. However, CB2's distal tip design could allow vein signals recording only in a minority of treated veins [ [16] , [17] , [18] ].…”
Section: Discussionmentioning
confidence: 99%
“…This difference may be explained by the higher rates of TTE observation in our CB3 group. A favourable TTE, known to be a good predictor of PV deconnection [ [14] , [15] , [16] , [17] ], allows to reduce the time of erogation. In fact, it's been demonstrated that TTE could be a good parameter to predict an optimal PV deconnection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is particularly a feature of cryoballoon ablation, where some degree of transient phrenic nerve dysfunction occurs in as many as 25% of cases, but clinically important injury occurs in fewer than 1% of cases. [ 17 ]…”
Section: Other Neural Injurymentioning
confidence: 99%